Preparation and characterisation of andrographolide niosomes and its anti-hepatocellular carcinoma activity. (June 2014) - Tu, Y. S.; Sun, D. M.; Zhang, J. J.; Jiang, Z. Q.; Chen, Y. X.; Zeng, X. H.; Huang, D. E.; Yao, N.
Abstract Objective: In this study, a novel andrographolide (AG) preparation formulation, niosomes, was prepared to improve the bioavailability and tissue distribution of AG. Methods: The niosomal formulation of AG was prepared by film hydration/sonication method and tissue distribution was measured by liquid chromatography-mass spectrometry (LC-MS) method in mice, and anti-hepatocellular carcinoma (anti-HCC) activity was examined by MTT method in HepG2. Results: Entrapment efficiency, drug-loading ratio and average particle size of AG niosomes were 72.36%, 5.90% and 206 nm, respectively. The tissue distribution in mice demonstrated that the AG niosomes were absorbed in liver much more than the free AG. Furthermore, the anti-HCC activity in HepG2 cells showed that there was no significant difference between free AG and AG niosomes. Conclusion: The present results suggest that AG niosomes may have a significant potential of liver targeting, which is valuable in chemotherapy of HCC.